2009
DOI: 10.1007/s10554-009-9515-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance T2 signal abnormalities in left ventricular ballooning syndrome

Abstract: Left ventricular ballooning syndrome (LVBS), also known as Takotsubo cardiomyopathy, is characterized by regional left ventricular dysfunction associated with severe psychological stress. T2 weighted cardiac magnetic resonance (CMR) can identify myocardial edema due to ischemia or other insults. A standard clinical CMR scan with double inversion recovery fast spin echo T2 weighted sequences was performed on consecutive patients with LVBS. T2 signal was compared in myocardial segments with normal and impaired f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…25 Furthermore, this modality provides information about the myocardium showing RWMA. 25, 26 The T2-weighted sequence usually reveals high signal intensity suggesting myocardial edema. Delayed enhancement with gadolinium, which suggests irreversible myocardial injury in AMI or myocarditis, is almost never detected in takotsubo cardiomyopathy.…”
Section: Cardiac Imagingmentioning
confidence: 99%
“…25 Furthermore, this modality provides information about the myocardium showing RWMA. 25, 26 The T2-weighted sequence usually reveals high signal intensity suggesting myocardial edema. Delayed enhancement with gadolinium, which suggests irreversible myocardial injury in AMI or myocarditis, is almost never detected in takotsubo cardiomyopathy.…”
Section: Cardiac Imagingmentioning
confidence: 99%
“…Interestingly, Joshi et al [16] reported that patients who had follow-up MR imaging at 2-3 weeks showed normalization of the wall motion abnormalities associated with a significant reduction in the T2 signal intensity. That finding is consistent with the MRI result of this current case.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated T2-signal consistent with myocardial edema is seen in patients with takotsubo cardiomyopathy. T2 signal is highest in myocardium with the most impaired function and resolves over time (21)(22). Myocardial edema on T2-STIR sequence is also a hallmark of ischemic myocardium prior to irreversible myocardial injury (23).…”
Section: Tissue Characterization -Myocardial Edema On T2-weighted Imagesmentioning
confidence: 99%